Indirect Approach to Mixed-Integer Optimal Control - Wu, Dongjun; Lin, Yankai (37th Chinese Control and Decision Conference, CCDC 2025, Xiamen, China, 2025-05-16 - 2025-05-19, 2025)
We study mixed-integer optimal control problem using indirect approaches. The proposed method relies on splitting algorithms which separate the mixed problem into two solvable pieces and then iteratively alternating between the two. The algorithm gives approximated local solutions, and provides lower and upper bounds estimations of the global optimum. Simulations are provided to validate our approach.
Keywords: mixed-integer constraints; Optimal control; splitting algorithm